Update 2013: the Role of Probiotic in Non-alcoholic Fatty Liver Disease, an Evidence Based Approach - Alvin Nursalim; Irsan Hasan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
During the last two decades, non-alcoholic fatty liver disease (NAFLD) has been a topic in many discussions. The major risk factors for NAFLD is metabolic syndrome, which include obesity, insulin resistance andhypertension. Beside insulin resistance, oxidative stress has been linked with the disease. There is accumulating evidence that intestinal bacterial overgrowth plays an important role in NAFLD pathogenesis. Intestinal bacteria influence the progression of NAFLD through endogenous ethanol production and cytokine that would eventually induce hepatic oxidative stress. Probiotic intervene pathogenic intestinal flora so it is a potential treatment for NAFLD. Many animal studies documented the beneficial effect of probiotic in NAFLD. Probiotic reduce hepatic inflammation, reduce hepatic steatosis and improve insulin resistance. There is still limited human studies upon this topic. However, preliminary result showed potential role of probiotic in NAFLD treatment. Probiotic is safe, cheap and widely available therefore it is a promising new approach for NAFLD therapy. Upcoming study would hopefully provide firm foundation regarding the use of probiotic for NAFLD on human.Keywords: NAFLD, probiotic, metabolic syndrome